Pension incentives and early retirement - Barbara Engels; Johannes Geyer; Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
In this paper we exploit a cohort-specific pension reform to estimate the causal labour market effects of changes in the financial incentives to retire. In particular, we analyze the effects of the introduction of cohort-specific deductions for early retirement on female retirement, employment and unemployment. For the empirical analysis we use high-quality administrative data from the German pension insurance. We present evidence for sizable labour market effects. In addition to direct effects on women older than 60 we find important anticipation effects before reaching the pension eligibility age. Overall we document that the pension reform leads to a postponement of retirement, an increase in employment and a shifting in unemployment over age rather than a substitution into unemployment.
Keywords: J14; J18; J22; J26; H21; 330; retirement age; pension reform; labour supply; actuarial deductions; cohort-specific pension reform; labour market effects